2016
DOI: 10.1186/s12891-016-1352-9
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with vancomycin-loaded calcium sulfate and vancomycin-loaded PMMA in the treatment of chronic osteomyelitis

Abstract: Background: Chronic post-traumatic and postoperative osteomyelitis is a refractory disease which results in significant morbidity and mortality. The effect of combination therapy with vancomycin-loaded calcium sulfate and vancomycin-loaded polymethyl methacrylate (PMMA) was unknown. Methods: Fifty-one patients suffering from chronic post-traumatic or postoperative osteomyelitis of the lower extremities were included in the retrospective investigation. The patients were assigned to the study group of the combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 37 publications
1
61
0
3
Order By: Relevance
“…Chronic osteomyelitis, especially resulting from multidrug‐resistant bacteria, is still a refractory disease and one of the major challenges for orthopedic surgeons, even though great progress has been made in surgical treatment and antibiotics for chronic osteomyelitis [1]. Local antibiotic‐loaded delivery systems are commonly adapted as effective vehicles for chronic osteomyelitis, to maintain antibiotics at a high level at the local site of osteomyelitis [2,3]. Antibiotics‐loaded poly(methyl acrylate, methyl methacrylate) (PMMA) was the effective antibiotic carrier system to control chronic osteomyelitis, because it can provide the following advantages: a high releasing level of antibiotics at the local site of infection, synchronously eliminating the surgically debridement‐derived dead space, low toxicity and less in serum [3–4].…”
mentioning
confidence: 99%
“…Chronic osteomyelitis, especially resulting from multidrug‐resistant bacteria, is still a refractory disease and one of the major challenges for orthopedic surgeons, even though great progress has been made in surgical treatment and antibiotics for chronic osteomyelitis [1]. Local antibiotic‐loaded delivery systems are commonly adapted as effective vehicles for chronic osteomyelitis, to maintain antibiotics at a high level at the local site of osteomyelitis [2,3]. Antibiotics‐loaded poly(methyl acrylate, methyl methacrylate) (PMMA) was the effective antibiotic carrier system to control chronic osteomyelitis, because it can provide the following advantages: a high releasing level of antibiotics at the local site of infection, synchronously eliminating the surgically debridement‐derived dead space, low toxicity and less in serum [3–4].…”
mentioning
confidence: 99%
“…Calcium sulfate absorbs plenty of water, which subsequently promotes seroma formation and increases the risk of secondary infection. 2 Our experience also showed that the calcium sulfate might not be completely degraded, causing a foreign body reaction in a small number of cases.…”
Section: Original Researchmentioning
confidence: 71%
“…Antibiotic-impregnated bone cement was introduced in the 1970s to treat infected arthroplasties, and antibiotic-impregnated beads have since been developed to treat local soft tissue and bone infections. 1,2 The advantage of antibiotic-containing beads is that they fill the dead space produced by sequestrectomy and bone curettage and the resulting local antibiotic concentrations vastly exceed the minimum inhibitory concentrations for most pathogens isolated in orthopaedic infections. 1,2,[6][7][8][9][10][11][12] Calcium sulfate can be loaded with antibiotics and used as a biodegradable medication delivery device.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations